Advancements in fuel cell technology for electric vehicles - Roslan, Mohammad Fikrey; Abd Rahman, Hamimah; Abd Karim, Rafidah; Osman, Siti Hasanah (Academica Press Solutions, 2024)
The field of electric vehicles (EVs) has seen significant advancements, particularly in the realm of fuel cell technology. This abstract explores the recent progress in fuel cell technology for EVs, focusing on the improvements in efficiency, durability, and cost-effectiveness. The primary challenge for EVs is to match the convenience and performance of traditional combustion engines while minimizing environmental impact. Battery Electric Vehicles (BEVs) face issues with long charging times and limited range, whereas Fuel Cell Electric Vehicles (FCEVs) have historically been hindered by high costs, low durability, and an underdeveloped hydrogen refueling infrastructure. Recent advancements in fuel cell technology have led to significant improvements in system efficiency, durability, and cost reduction. Innovations in catalysts and membrane electrode assemblies have enhanced the electrochemical conversion efficiency, while novel materials and manufacturing techniques have extended the lifespan and reduced the costs of fuel cells. The enhanced performance of fuel cells has resulted in EVs with longer ranges and refueling times comparable to conventional vehicles. This has a profound impact on the feasibility of EVs for a broader range of applications, including heavy-duty transportation and long-distance travel. The advancements in fuel cell technology have lowered the barriers to commercialization. With increased efficiency and reduced costs, FCEVs are becoming more competitive with both BEVs and traditional vehicles. The growing network of hydrogen refueling stations further supports the commercial viability of FCEVs. The recent advancements in fuel cell technology have addressed critical challenges in the EV industry, offering a solution that combines environmental benefits with performance and convenience. As the technology continues to mature and the infrastructure expands, FCEVs are poised to play a pivotal role in the transition to sustainable transportation, promising a cleaner future with reduced reliance on fossil fuels.